The Implementation of South Korea-Indonesia Defense Diplomacy in the Shifting Defense Industrial Cooperation in the Chang Bogo-Class Submarine Project 2019-2023 - Kim, Joodael; Wenas Inkiriwang, Frega F.; Banyu Perwita, Anak Agung (Aksaqila International Humanities and Social Sciences [AIHSS] Journal, 2025)
This study examines the dynamic of South Korea-Indonesia defense industrial cooperation from 2019 to 2023, focusing on the Chang Bogo-class submarine project. The research is motivated by shifts in defense priorities between the Yudhoyono and Jokowi administrations, particularly regarding modernization, economic resilience, and budget efficiency. While the Yudhoyono government emphasized joint production and technology transfer, the Jokowi administration's focus on fiscal constraints led to adjustments in the scale and pace of collaboration. This study aims to analyze these shifts and their impact on bilateral defense relations. To achieve this, five theoretical frameworks—International Relations Theories, Foreign Policy, Defense Policy, Defense Diplomacy, and Defense Industry—are applied to provide a comprehensive evaluation. The research employs policy reviews, case studies, and analyses of defense agreements and official reports to assess the underlying factors influencing cooperation. The findings indicate that economic limitations, evolving foreign policy goals, and differing leadership approaches have affected project progress. However, sustained defense diplomacy, including high-level meetings and strengthened agreements, has helped maintain collaboration despite these challenges. The study concludes that aligning defense cooperation with political and economic realities is essential for sustainability. Recommendations include improving financial strategies in joint projects, implementing phased technology transfer, and strengthening institutional frameworks to ensure long-term defense partnerships. By addressing these areas, South Korea and Indonesia can enhance their defense collaboration, contributing to regional security and capability development. This research highlights the importance of adaptive defense diplomacy in maintaining strategic partnerships amid shifting national priorities.